KEBERADAAN DAN FUNGSI PENDIDIKAN ISLAM DALAM ERA POSMODERNISME - Sultani B Silalahi; Mujahiddin Sujarnas Pohan; Nita Fauziah; Nur’ainun Arnasti (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Posmodernisme is a new intellectual cultural movement that arose because of unciouse feeling to the hope of modern movement failed in getting the aim of human being prosperous. Posmodernism refused the concept of science and technology in modernist nearly be pseudo-religion. In perspective of religious thinker, it occured because of methafisic dimention an religiousity in human existention has been forgetten, as moral an normative ethics are not in modern era. Based on this the roles of Islamic education become centre as a function of human protector from the effect of secularism issue in modernist.